STUDY OF THE EDUCATION FOR INNOVATION PROGRAM IN DIGITAL INDUSTRY 4.0: AGILE PROJECT METHODOLOGY MULTI-CASE STUDY (ONESUBSEA - FAE) - Eduarda Szymczak, Maria; Paula Lopes de Souza, Gilson (Caderno PAIC, 2024)
This article explores the dynamics between academia and industry in the innovation of Industry 4.0, focusing on Production Engineering and Mechanical Engineering courses. As a second phase, considering the previous project "Education for Innovation in the Context of Industry 4.0" (LUZ et al., 2023), the research concentrates on identifying measures taken to improve the ability of educational and corporate institutions to keep up with innovations in Industry 4.0, to incorporate innovation as part of the organizational culture. Furthermore, the research studies the gaps identified in the previous PAIC carried out in partnership with Onesubsea and Centro Universitário FAE, following the requirements of the ISO 56.002 standard and the Agile Project Management Methodology. In parallel, a study will be conducted on the academic market of engineering courses and its compatibility with market demands. The article will benefit academia and companies in their educational, productive, and administrative processes, creating an environment conducive to innovation and implementing Agile Project Management in the face of the challenges of Industry 4.0.